Treatment with abatacept prevents experimental dermal fibrosis and induces regression of established inflammation-driven fibrosis. Issue 12 (24th February 2016) - Ponsoye, Matthieu; Frantz, Camelia; Ruzehaji, Nadira; Nicco, Carole; Elhai, Muriel; Ruiz, Barbara; Cauvet, Anne; Pezet, Sonia; Brandely, Marie Laure; Batteux, Frédéric; Allanore, Yannick; Avouac, Jérôme
Abstract : Objective: Activated T cells are the main component of the inflammatory skin infiltrates that characterise systemic sclerosis (SSc). Our aim was to investigate the efficacy of abatacept, which tempers T-cell activation, in reducing skin fibrosis in complementary mouse models of SSc. Methods: The antifibrotic properties of abatacept were evaluated in the mouse models of bleomycin-induced dermal fibrosis and sclerodermatous chronic graft-versus-host disease, reflecting early and inflammatory stages of SSc. Thereafter, we studied the efficacy of abatacept in tight skin (Tsk-1) mice, an inflammation-independent mouse model of skin fibrosis. Results: Abatacept efficiently prevented bleomycin-induced skin fibrosis and was also effective in the treatment of established fibrosis. In this model, abatacept decreased total and activated T-cell, B-cell and monocyte infiltration in the lesional skin. Abatacept did not protect CB17-SCID mice from the development of bleomycin-induced dermal fibrosis, which supports that T cells are necessary to drive the antifibrotic effects of abatacept. Upon bleomycin injections, skin interleukin (IL) 6 and IL-10 levels were significantly reduced upon abatacept treatment. Moreover, treatment with abatacept ameliorated fibrosis in the chronic graft-versus-host disease model, but demonstrated no efficacy in Tsk-1 mice. The tolerance of abatacept was excellent in the three mouse models. Conclusions: Using complementary models, we demonstrate that inhibition of T-cell activation by abatacept can prevent and induce the regression of inflammation-driven dermal fibrosis. Translation to human disease is now required, and targeting early and inflammatory stages of SSc sounds the most appropriate for positioning abatacept in SSc.